Effects of mosquito-proofing storm drains on adult and larval mosquito abundance: Protocol of the IDAlErt storm drAin randomiSed controlled trial (IDEAS) - Marina Treskova; Tomás Montalvo; Joacim Rocklöv; Charles Hatfield; Frederic Bartumeus; Shouro Dasgupta; João Encarnação; Rachel Lowe; Jan C. Semenza; Pascale Stiles; Jordi Noya; Andrea Valsecchi; et al. (MethodsX)
Aedes and Culex mosquitoes, known for spreading arboviruses like dengue and West Nile, thrive in cities, posing health risks to urban populations. Climate change can create suitable climatic conditions for these vectors to spread further in Europe. Cities contain numerous landscape and infrastructure elements, such as storm drains, that allow stagnant water build-up, facilitating mosquito breeding. Modifying urban infrastructure to prevent water accumulation can reduce mosquito populations, but evidence is limited. The Agència de Salut Pública de Barcelona (ASPB), which is the public health agency of Barcelona, Spain, recently introduced a structural modification of storm drains to prevent water accumulation. Together with the ASPB, we designed a randomised controlled trial (RCT) to experimentally assess the effectiveness of these modifications on adult Aedes albopictus and Culex pipiens populations. Using a parallel-arm RCT, we equally randomized 44 drains to receive mosquito-proofing modifications (intervention) or not (control). We measured adult mosquito counts as the primary outcome and adult and larvae presence as secondary outcomes, sampling each drain weekly from June through November 2023. We will use generalised linear mixed models to estimate the time-averaged and peak mosquito month intervention effects, and conducted complimentary subgroup and sensitivity analyses. The trial results will guide potential city-wide expansion of storm drain modifications and provide valuable evidence to enhance existing vector control measures.